2015
DOI: 10.15230/scsk.2015.41.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bambusae Caulis in Taeniam Extract on the UVB-induced Cell Death, Oxidative Stress and Matrix Metalloproteinase 1 Expression in Keratinocytes

Abstract: Ultraviolet radiation (UV) is a major cause of skin photoaging, and effective UV protecting agents are needed for the skin health and beauty. This study was undertaken to examine the effects of Bambusae caulis in Taeniam extract (BCTE) on UVB-induced cell death, oxidative stress and matrix metalloproteinase 1 (MMP1) expression in cell-based assays. HaCaT human keratinocytes were exposed to UVB in the presence of BCTE at different concentrations and resulting changes in cell viability and biochemical events wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…HaCaT cells (a human immortalized keratinocyte cell line) were grown in Dulbecco's modified Eagle's medium/F-12 medium (GIBCO-BRL, Grand Island, NY, USA) supplemented with 10% fetal bovine serum, 100 U mL À1 penicillin, 0.1 mg mL À1 streptomycin, 0.25 μg mL À1 amphotericin B, and 10 μg mL À1 hydrocortisone. For experiments requiring UV exposure, HaCaT cells were seeded in a six-well plate at a density of 3 × 10 5 cells per well and grown for 24 h. Cells were then irradiated with UVB in phosphate buffered saline containing a test material at the specified concentrations, as previously described (Park et al, 2014;Seok et al, 2015). Irradiated cells were cultured with a growth medium for 24 h. Cell viability was determined using 3-[4,5-dimethylthiazol-2yl]-2,5-diphenyltetrazolium bromide (Park et al, 2014;Seok et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…HaCaT cells (a human immortalized keratinocyte cell line) were grown in Dulbecco's modified Eagle's medium/F-12 medium (GIBCO-BRL, Grand Island, NY, USA) supplemented with 10% fetal bovine serum, 100 U mL À1 penicillin, 0.1 mg mL À1 streptomycin, 0.25 μg mL À1 amphotericin B, and 10 μg mL À1 hydrocortisone. For experiments requiring UV exposure, HaCaT cells were seeded in a six-well plate at a density of 3 × 10 5 cells per well and grown for 24 h. Cells were then irradiated with UVB in phosphate buffered saline containing a test material at the specified concentrations, as previously described (Park et al, 2014;Seok et al, 2015). Irradiated cells were cultured with a growth medium for 24 h. Cell viability was determined using 3-[4,5-dimethylthiazol-2yl]-2,5-diphenyltetrazolium bromide (Park et al, 2014;Seok et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…For experiments requiring UV exposure, HaCaT cells were seeded in a six‐well plate at a density of 3 × 10 5 cells per well and grown for 24 h. Cells were then irradiated with UVB in phosphate buffered saline containing a test material at the specified concentrations, as previously described (Park et al ., ; Seok et al ., ). Irradiated cells were cultured with a growth medium for 24 h. Cell viability was determined using 3‐[4,5‐dimethylthiazol‐2‐yl]‐2,5‐diphenyltetrazolium bromide (Park et al ., ; Seok et al ., ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferulic acid, a phenolic compound structurally similar to p-CA, has been previously shown to suppress ultraviolet B radiation-induced MMP expression in mouse skin [32]. Our recent study also showed that p-CA suppressed the expression of MMP1 and the phosphorylation of c-Jun N-terminal kinase in HaCaT keratinocytes exposed to ultraviolet radiation [28]. Thus, p-CA might regulate the signaling pathways that induce MMP1 expression.…”
Section: Discussionmentioning
confidence: 59%
“…UV rays induce apoptosis of keratinocytes via intrinsic pathways, involving direct DNA damage; extrinsic pathways, involving activated cell membrane death receptors; and other ROS-mediated pathways [ 38 , 40 ]. Apoptosis can be detected using various markers, including DNA laddering, changes in the expression of pro-apoptotic (Bax, Bak, and Bid) and anti-apoptotic (Bcl-2 and Bcl-x) members of the Bcl-2 protein family, and activation of caspases [ 41 , 42 , 43 ].…”
Section: Uv-induced Toxicity In the Skinmentioning
confidence: 99%